IMPLEMENTASI TENTANG PERCEPATAN PENCATATAN PERKAWINAN DALAM PP NO 9 TAHUN 1975 TENTANG PELAKSANAAN UU NO 1 TAHUN 1974 TENTANG PERKAWINAN (Studi Kasus Di Kantor Urusan Agama Kec.Diwek Kabupaten Jombang) - M Ashar Al Anshori; Habibi Al Amin (Kampus Akademik Publiser, 2024)
This research was motivated by Government Regulation Number 9 of 1975 concerning requirements that must be fulfilled by prospective brides and grooms who will carry out marriage registration. Namely Chapter II Article 3 Paragraph 3 PP No. 9 of 1975 The exception to this time period is due to an important reason, given by the District Head on behalf of the Regent, This means that there is still a gap provided if the waiting period of ten working days before the marriage takes place cannot be implemented for an important reason, namely by speeding up the registration of marriages, which should be recorded in 10 working days to less than that. Note that you must obtain written permission from the local sub-district head on behalf of the regent Research problem formulation, this is the reason why prospective brides and grooms propose to accelerate the acceleration of marriage registration and legal implementation of Republic of Indonesia Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 Chapter II concerning Marriage Registration Article 3 Paragraph 3 at the Religious Affairs Office, Diwek District, Jombang Regency. This research is a type of research using field research, namely the researcher makes KUA, sub-district heads and candidates the bride and groom who applied for acceleration (dispensation) from the sub-district head. The data collection techniques use techniques. interviews, observation and documentation. The conclusion from the results of this research is that there are several factors that cause prospective brides and grooms to request accelerated marriage registration. Namely the economic factor. The prospective bride and groom will carry out a wedding which is used as an event moment along with their proposal in order to save financial expenses but are late in submitting their will or registering the marriage which must be more than 10 working days (more than two weeks) before the event. The cultural factor is that the marriage was registered and it took more than 10 working days and suddenly someone in the family died and asked for the marriage to be expedited before the body was buried. There is also the phenomenon of getting pregnant first which is included in the benefit factor, namely that prospective brides who become pregnant first will have their marriage registration expedited for an important reason, namely easing the moral burden on the family and saving the fetus in the womb. Implementation of accelerated marriage registration in PP No. 9 of 1975 Chapter II Article 3 Paragraph 3 in the KUA of Diwek District is in accordance with applicable regulations, but many people do not know about these procedures.